Evaluasi Kinerja Pompa Sentrifugal NO. 3 Pada RPKS II Di PPSDM Migas Cepu - Salmon, Maurenzia; Pattykayhattu, Erwin. B.; Pattiasina, Nanse. Henny. (Journal Mechanical Engineering, 2024)
The research objectives are to identify the performance efficiency of Centrifugal Pump No. 3, determine the headloss value, and compare the available NPSH with the required one. The method used is quantitative with an experimental approach to collect pump performance data. The results showed that the pump performance efficiency was 9.9%, headloss was 0.003521 m, total pump head = 9.19 m, hydraulic power = 0.49 kW, pump power = 5.1 kW, available NPSH was 9.92 and the required NPSH was 2.3 m. The application of preventive maintenance includes identifying components experiencing wear and tear, periodic maintenance of suction and discharge piping, routine purging to reduce head losses and checking the condition of the pump suction to anticipate cavitation factors. The application of preventive maintenance includes identifying components that are experiencing wear and tear, periodic maintenance of suction and discharge pipe installation, routine flushing to reduce head losses and inspection of pump suction conditions to anticipate the cavitation factor. Keywords: centrifugal pump, PPSDM, head loss, preventive maintenance